Correlation of charge transport with structural order in highly ordered melt‐crystallized poly(3‐hexylthiophene) thin films. Issue 12 (23rd April 2013) - Singh, Chetan R.; Gupta, Gaurav; Lohwasser, Ruth; Engmann, Sebastian; Balko, Jens; Thelakkat, Mukundan; Thurn‐Albrecht, Thomas; Hoppe, Harald
ABSTRACT A series of well‐defined poly(3‐hexylthiophene)s (P3HT) of different molecular weight (MW) and high regioregularity was investigated for charge transport properties in as‐cast and melt‐crystallized films. The semicrystalline structure of the P3HT was characterized by X‐ray scattering and Atomic force microscopy. Crystallization by cooling from the melt led to a substantial increase in crystallinity and a stronger alignment of the crystals in comparison to as‐cast films. The increase in crystallinity went along with an increase in hole mobility of up to an order of magnitude as measured by the space charge limited current method. Additionally, the hole mobility depended on the long period of P3HT lamellae and consequently on the MW. In compliance with the long period, the charge carrier mobility first increased with the MW before decreasing again at the onset of chain folding. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2013, 51, 943–951